Endometrial Polyps in Women Affected by Levothyroxine-Treated Hypothyroidism—Histological Features, Immunohistochemical Findings, and Possible Explanation of Etiopathogenic Mechanism: A Pilot Study. (22nd August 2013) - Saccardi, Carlo; Gizzo, Salvatore; Ludwig, Kathrin; Guido, Maria; Scarton, Mara; Gangemi, Michele; Tinelli, Raffaele; Litta, Pietro Salvatore
Abstract : The aim of the study was to investigate the possible overexpression of estrogen (ERs) and progesterone (PRs) receptors both in EPs glandular and stromal cells in postmenopausal women with levothyroxine-treated hypothyroidism in comparison to EPs detected in women with physiological thyroid hormone levels. During the study period (January-February 2013) 22 patients were eligible (12 treated, 10 controls). The two groups were homogenous for general, EPs sonographic and hysteroscopic features. None of the cases of atypia was found. Immunohistochemistry showed that the two groups were similar for ERs and PRs intensity rates in EPs glandular cells despite a trend of ERs percentage expression more than 60% in 2/3 of treated patients versus 1/3 of controls. In stromal EPs components, ERs intensity was high positive in 10 (83, 3%) treated cases while it was high positive in 1 control (10%). Percentage of ERs stromal expression showed a different trend between the two groups despite a borderline statistical significance. Our hypothesis is based on a possible double action of hypothyroidism and thyroxine intake: the subclinical TSH increased levels and its possible circadian oscillation could stimulate the endometrial TSHRs (increasing type 2 DIO activity); the circulating levels of exogenous thyroxine could be locally metabolized in active form by type 2 DIO stimulating ERs.